The Speaking English Problems Faced by the Fourth Semester Students of English Education Study Program UKI Toraja - Sushy Teko Patanduk (Teaching English as a Foreign Language Overseas Journal, 2019)
The objective of this research is to find out the problem faced by the fourth semester students of UKI TORAJA in speaking English. This research used qualitative method. The population of this research is the fourth semester students of English Department of UKI Toraja. The writer used purposive sampling to choose the participant. The writer chose 10 of students as a participant. To collect the data, the writer used observation and interview. The writer used semi structure interview. The result of the data analysis collected through observation and interview showed that the fourth semester students of English department of UKI Toraja have problems in speaking when they want to speak in English. They are fear of make mistake, fear of being criticized, shyness, nothing to say, low or uneven participant, anxiety, poor in pronunciation, poor in grammar, difficulty in verbal expression, lack of motivation and interference of mother tongue.